Health technology assessment in low‐ and middle‐income countries: a landscape assessment. Issue 1 (3rd January 2016) - Babigumira, Joseph B.; Jenny, Alisa M.; Bartlein, Rebecca; Stergachis, Andy; Garrison, Louis P.
Abstract: Objectives: Health technology assessment (HTA) for a wide range of healthcare technologies is an essential component of well‐functioning health systems. Knowledge of the use of HTA in low‐ and middle‐income countries (LMICs) is limited. Methods: We performed a survey of HTA in selected LMICs. We interviewed key stakeholders on the use, conduct and challenges of performing HTA in their countries. We performed mixed‐methods analyses to identify, characterize and describe HTA and how it relates to gross domestic product and government effectiveness. Key findings: Of the 19 countries selected for participation, stakeholders in 12 (63%) countries responded to the survey – Afghanistan, Bangladesh, Democratic Republic of Congo (DR Congo), Dominican Republic, Ethiopia, Jordan, Kenya, Namibia, Rwanda, South Africa, Swaziland and Vietnam. Eight countries surveyed have some form of informal HTA activity conducted by stakeholders including academia, industry, government and the World Health Organization. There is evidence of knowledge sharing with five countries using HTAs from their neighbouring countries or from more developed countries. We found no evidence of formal HTA performed through dedicated, independent bodies in the LMICs surveyed. There was some evidence that HTA was moderately related to GDP per capita and strongly related to degree of centralization (government effectiveness). Respondents identified resources, both financial and human, as challenges to conducting HTA. Conclusions: Formal HTA appears to be non‐existent or limited in the LMICs surveyed but some evidence of informal HTA exists. Efforts to formalize HTA and to use existing HTA evidence will improve the quality of regulatory, coverage, formulary and reimbursement decisions, and individual and public health.